Analysis of prolactin and sexual side effects in patients with schizophrenia who switched from paliperidone palmitate to aripiprazole lauroxil. (August 2021) - Kelly, Deanna L.; Claxton, Amy; Bidollari, Ilda; Du, Yangchun
Highlights: This study evaluated switching from paliperidone palmitate to aripiprazole lauroxil. In a post hoc analysis, prolactin levels and sexual side effects were evaluated. Prolactin levels decreased over the 6 months after switch to aripiprazole lauroxil. Proportion of patients with high prolactin was 98% at screening and 6.3% at month 6. Modest improvements in sexual side effects were also evident after switching. Abstract: One strategy to address hyperprolactinemia and associated sexual side effects in patients receiving antipsychotics is switching to an antipsychotic not associated with prolactin elevation (eg, aripiprazole). This post hoc analysis assessed prolactin concentrations and sexual side effects in an open-label prospective study of switching long-acting injectable antipsychotics from paliperidone palmitate (PP) to aripiprazole lauroxil (AL). Serum prolactin was measured throughout the study. Patient-reported sexual and endocrine side effects were assessed on the UKU Side Effect Rating Scale sexual function subscale and analyzed in study completers. Prior to starting AL treatment (screening), 49/50 (98%) patients had prolactin concentrations above the upper limit of normal (ULN; >13.13 ng/mL [males]; >26.72 ng/mL [females]). Six months after beginning AL treatment, prolactin levels were above ULN in 2/32 (6.3%) patients. Among 32 study completers, 81.3% reported sexual dysfunction in ≥1 domain at screening versus 56.3% at 6 months after starting AL treatment. Diminished sexual desire was the most common patient-reported sexual complaint at screening (46.9%); at 6 months, it was reported by 18.8%. In this post hoc analysis, the high levels of prolactin observed at screening decreased during AL treatment, and modest improvements in sexual side effects were evident in patients with schizophrenia.